Determination of soil properties for plane strain condition from the triaxial tests results. (9th January 2015) - Nanda, S.; Patra, N. R.
Summary Significant difference in stress–strain behavior of dense cohesionless soil has been observed between plane strain and triaxial test conditions. At present, majority of geotechnical laboratories have no plane strain testing facility. Therefore, geotechnical professionals are more dependent on the conventional triaxial test for soil properties, whereas many geotechnical structures prevail close to plane strain condition. A method has been proposed to determine soil properties for plane strain condition from the conventional triaxial tests. This method can especially be used to determine the internal friction angle and stress–strain relationship for plane strain condition from triaxial tests results. Copyright © 2015 John Wiley & Sons, Ltd.